Development of Technology and Popularization of Biological Control Agents for Integrated Management of Coconut Leaf Rot Disease - Srinivasan, N.; Chandramohanan, R.; Bharathi, R.; Radhika, N. S.; Issak, Shanty (International Coconut Community, 2011)
Coconut is an important social crop of livelihood concern for millions of small- medium farmers. Leaf rot disease (due to a fungal complex-Colletotrichum gloeosoprioides, Exserohilum rostratum and Fusarium solani as major pathogens), in association with root (wilt), is a major problem of coconut in southern districts of Kerala besides certain districts in Tamil Nadu etc. Central Plantation Crops Research Institute (CPCRI) has evolved biological control technology for integrated management of leaf rot to improve the health of disease affected palms. Application of biocontrol agents in the disease affected areas was aimed for creation of widespread awareness on eco-friendly disease management, crop sustenance and in realizing human resource potential. Effective strains of biocontrol agents-Bacillus subtilis, Pseudomonas fluorescens and Trichoderma viride-were evolved, their multiplications in media including coconut water standardized and the antagonists’ processed into bioformulations (totally 2000 Kg. talc formulations evolved distributed/utilized). Coconut gardens and rural groups in various districts of southern Kerala (Thiruvananthapuram, Kollam, Alappuzha, Pathanamthitta, Kottayam, Idukki, Ernakulam and Thrissur), various blocks in Theni district besides specified blocks in Dindigul district of Tamil Nadu could be selected. Through effective contacts with extension-developmental agencies, coconut Research & Development (R&D) meetings etc. reached out to rural people and implemented the technology of mass production-use of biological control agents, and knowledge imparted to rural people. Conducted trainings and allied programmes by on-campus trainings (396 beneficiaries), off-campus trainings (1854 beneficiaries), household/field contacts of rural people (689 beneficiaries) and other awareness programmes encompassing lectures, interfaces etc. (661 beneficiaries) and enlightened women, rural people, youths etc. representing various locations (totally 3600 beneficiaries in three years). Field demonstrations of disease management with biological control agents in coconut gardens (55 units) besides clusters-compact gardens (1850 coconut palms) were also done. Also, promotional materials were made available to various stakeholders. An innovative participatory programme implementation approach for technology transfer was the outcome of the work. Creation of widespread awareness, percolation of knowledge on biocontrol agents to women and other rural people could be visualized that would go a long way.